2004
DOI: 10.1002/nbm.906
|View full text |Cite
|
Sign up to set email alerts
|

First‐pass and equilibrium‐MRA of the aortoiliac region with a superparamagnetic iron oxide blood pool MR contrast agent (SH U 555 C): results of a human pilot study

Abstract: The purpose of this study was to study different doses for first-pass and equilibrium phase MRA of aortoiliac vessels with a superparamagnetic iron oxide (SPIO) intravascular MR contrast agent (SH U 555 C) after single i.v. bolus injection. Sixteen healthy volunteers were prospectively enrolled into this single-blind, placebo-controlled clinical trial. SHU 555 C was injected as an i.v. bolus at stepwise increased dose levels of 5, 10, 20 and 40 mmol Fe/kg bodyweight (b.w.) corresponding to injection volumes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 34 publications
1
31
0
Order By: Relevance
“…Blood pool agents, i. e. intravascular contrast agents including SupravistÔ remain in the blood compartment for a prolonged period of time compared to conventional contrast agents, which diffuse quickly into the interstitial space. Magnetic resonance angiography, cardiovascular imaging, or contrast enhanced MRI are possible over an hour or more upon intravascular injection of such a contrast agent [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Blood pool agents, i. e. intravascular contrast agents including SupravistÔ remain in the blood compartment for a prolonged period of time compared to conventional contrast agents, which diffuse quickly into the interstitial space. Magnetic resonance angiography, cardiovascular imaging, or contrast enhanced MRI are possible over an hour or more upon intravascular injection of such a contrast agent [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The USPIO SHU 555 C has been proposed for CE-MRA and allows in contrast to Ferumoxtran-10, for first-pass CE-MRA [32]. In a study of the aorto-iliac vessels by Tombach et al [32] SHU 555 C proved to be a contrast agent with a high T1-effect suitable for both first-pass MRA comparable to gadoliniumenhanced MRA and high resolution equilibrium MRA up to 42 min post-injection. Accordingly, our results showed a diagnostic relevant image quality for first-pass CE-MRA of the supra-aortal vessels.…”
Section: Discussionmentioning
confidence: 97%
“…Due to prior performance of first-pass CE-MRA, the early plaque perfusion was missed. Another possible approach is to perform DCE-MRI first, followed by equilibrium CE-MRA, which has been reported to be diagnostic for the aorto-iliac region [32], but is yet to be proven for the supra-aortal vessels. USPIO suffer in general from very low absolute T1-w signal enhancement due to low rates of contrast agent extravasation [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This technique improved significantly the signal-to-noise ratio, particularly in anatomical cortical vascular imaging (Burgess et al, 1999), by achieving resolutions of vessels of around 100 mm in diameter (Dashner et al, 2004). In combination with ultrasmall superparamagnetic iron oxide (USPIO) blood pool contrast agents which remain intravascular for a long period of time (Weissleder et al, 1990;Tombach et al, 2004), an improved capability of data in terms of resolution can be achieved. In a study of Christoforides et al, (Christoforidis et al, 2009) not only vessels with diameters of 20 mm were identified after USPIO administration in an UHF MRI approach but also the state of hypoxia within the tumor was determined.…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%